Rethinking social transformation - Giri, Ananta Kumar.(ed.) (Jaipur, 2001)
The volume is dedicated jointly to Shri Sunderlal Bahuguna, Prof. Daya Krishna, Prof. Manoranjan Mohanty and Prof. Ashis Nandy. They have, in their own unique ways, combined activist engagements with deep reflections and have helped us rethink social transformation and initiate new path Ways of criticism and creativity. As a leading participant in the ways famous Chipko movement in the Himalayas, Sunderlaljee has stirred the conscience of the world about issues of ecological re- sponsibilities. His critical engagements continue unabated even in his ripe age and in these new times of quick conformity to the idols of the market place. I recall vividly my meeting with him in July 1987 when we spent two days together in his ashram at Silvara near Tehri. During our discussion Sunderlaljee had pointed out to me the great danger that lies in leaving the task of social reconstruction in the hands of paid workers and processionals. In these days of corporatization of the much voluntary sector, even in a country like India, we shall do well to listen to the lone and courageous voice of crusaders like Sunderlaljee.
Keywords: Social transformation